2019
DOI: 10.1016/j.nicl.2019.101694
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate weighted imaging contrast in gliomas with 7 Tesla magnetic resonance imaging

Abstract: Introduction Diffuse gliomas are incurable malignancies, which undergo inevitable progression and are associated with seizure in 50–90% of cases. Glutamate has the potential to be an important glioma biomarker of survival and local epileptogenicity if it can be accurately quantified noninvasively. Methods We applied the glutamate-weighted imaging method GluCEST (glutamate chemical exchange saturation transfer) and single voxel MRS (magnetic resonance spectroscopy) at 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 61 publications
2
60
0
Order By: Relevance
“…Evaluation in epilepsy patients indicated a higher GluCEST signal in the hippocampus ipsilateral to the location of seizure onset, again suggesting an increase in glutamate levels during the interictal phase [143]. Furthermore, increased peritumoral GluCEST contrast in glioma patients was associated with both recent seizures and drug-refractory epilepsy [144]. Taken together, the evidence reported in these studies indicates that an increase in glutamate tone is important for the establishment of irritable status in epilepsy.…”
Section: Background Irritabilitymentioning
confidence: 60%
“…Evaluation in epilepsy patients indicated a higher GluCEST signal in the hippocampus ipsilateral to the location of seizure onset, again suggesting an increase in glutamate levels during the interictal phase [143]. Furthermore, increased peritumoral GluCEST contrast in glioma patients was associated with both recent seizures and drug-refractory epilepsy [144]. Taken together, the evidence reported in these studies indicates that an increase in glutamate tone is important for the establishment of irritable status in epilepsy.…”
Section: Background Irritabilitymentioning
confidence: 60%
“…Excessive accumulation of extracellular Glu induces excitotoxicity in CNS neurons, which may lead to various brain disorders, such as epilepsy, schizophrenia, depression, tumors, etc. (Davis et al, 2015;Roalf et al, 2017;Neal et al, 2019;Kaminski et al, 2020). It was also recently reported that glutamate is closely implicated in microglial activation and that activated microglia play a key role in encephalitis.…”
Section: Discussionmentioning
confidence: 97%
“…recently demonstrated that increased peritumoural GluCEST contrast is associated with both recent seizures and drug refractory epilepsy in patients with glioma (Fig. 2) (75).
Fig.
…”
Section: Glutamatementioning
confidence: 85%
“…Axial GluCEST image (right) demonstrating increased GluCEST contrast in a glioma patient. From Neal et al (2019).…”
Section: Glutamatementioning
confidence: 99%